Statistical inference of earlier origins for the first flaked stone technologies. Issue 154 (May 2021) - Key, Alastair J.M.; Roberts, David L.; Jarić, Ivan
Abstract: Identifying when hominins first produced Lomekwian, Oldowan, and Acheulean technologies is vital to multiple avenues of human origins research. Yet, like most archaeological endeavors, our understanding is currently only as accurate as the artifacts recovered and the sites identified. Here we use optimal linear estimation (OLE) modelling to identify the portion of the archaeological record not yet discovered, and statistically infer the date of origin of the earliest flaked stone technologies. These models provide the most accurate framework yet for understanding when hominins first produced these tool types. Our results estimate the Oldowan to have originated 2.617 to 2.644 Ma, 36, 000 to 63, 000 years earlier than current evidence. The Acheulean's origin is pushed back further through OLE, by at least 55, 000 years to 1.815 to 1.823 Ma. We were unable to infer the Lomekwian's date of origin using OLE, but an upper bound of 5.1 million years can be inferred using alternative nonparametric techniques. These dates provide a new chronological foundation from which to understand the emergence of the first flaked stone technologies, alongside their behavioral and evolutionary implications. Moreover, they suggest there to be substantial portions of the artifact record yet to be discovered.